2017
DOI: 10.1186/s12936-017-1681-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient method for establishing F1 progeny from wild populations of Anopheles mosquitoes

Abstract: BackgroundThe changing malaria situation in Madagascar requires additional knowledge on the physiology and behaviour of local mosquito vectors. However, the absence of established colonies for several anopheline species present in Madagascar constitutes a limiting factor. To avoid labour intensive work and uncertainty for success of establishing Anopheles colonies from Malagasy species, field collections of blood-fed females and in-tube forced oviposition were combined to reliably produce large numbers of F1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…A previous study measuring the fecundity of F 1 An. funestus using Madagascan population reported that this species can lay and average of 56 to 108 eggs per mosquito in captivity [35], which corroborate with 65 and 76 eggs from wild-FUTAZ and FUMOZ respectively from the current study. The number of eggs here is consistent to that reported in resistant and susceptible An.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study measuring the fecundity of F 1 An. funestus using Madagascan population reported that this species can lay and average of 56 to 108 eggs per mosquito in captivity [35], which corroborate with 65 and 76 eggs from wild-FUTAZ and FUMOZ respectively from the current study. The number of eggs here is consistent to that reported in resistant and susceptible An.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, poor hatching observed in the nascent strain (FUTAZ) here is likely due to the low mating success of An. funestus in captivity as has been previously documented in other Anopheles species [35].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While, to our knowledge, this is the first demonstration that the stress-responsive JNK pathway is involved in an important reproductive behavior such as oviposition, egg laying has been previously linked to stress responses in mosquitoes. Stressful stimuli including heat, dessication, starvation and infection have all been shown to impact on the timing of oviposition (Canyon et al, 1999; Shaw et al, 2016; Sylvestre et al, 2013), whereas confinement stress has been hypothesized to increase the frequency of oviposition in various anophelines (Nepomichene et al, 2017). Links between steroid hormones and stress responses have also been documented (Hirashima et al, 2000; Ishimoto and Kitamoto, 2010; Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After morphological identification [ 25 ], one hundred and eighty-six (186) blood fed An . funestus were individually transferred into a tube (Eppendorf®) for forced oviposition according to the method described by Nepomichene et al [ 26 ]. In brief, female mosquitoes were maintained at 28°C in 75-80% relative humidity with free access to 10% sucrose until they became fully gravid (about four days) and individually placed inside a tube with a filter paper placed at the bottom.…”
Section: Methodsmentioning
confidence: 99%